Coding of odors by temporal binding within a model network of the locust antennal lobe - Patel, Mainak J.; Rangan, Aaditya V.; Cai, David (Frontiers in Computational Neuroscience, 2013)
The locust olfactory system interfaces with the external world through antennal receptor neurons (ORNs), which represent odors in a distributed, combinatorial manner. ORN axons bundle together to form the antennal nerve, which relays sensory information centrally to the antennal lobe (AL). Within the AL, an odor generates a dynamically evolving ensemble of active cells, leading to a stimulus-specific temporal progression of neuronal spiking. In order to study information coding within the locust AL, we developed a scaled-down model of the locust AL using Hodgkin Huxley-type neurons and biologically realistic connectivity parameters and current components. Using our model, we examined correlations in the precise timing of spikes across multiple neurons. We propose that the dynamical interplay of fast and slow inhibition within the locust AL induces correlations in the spiking activity of an odor-dependent neural subset, giving rise to a temporal binding code that allows rapid stimulus detection by downstream elements.